A Risk Analysis of Adjusted Gross Revenue-Lite on Beef Farms. (May 2014) - Williams, Jeffery R.; Saffert, Andrew T.; Barnaby, G. Art; Llewelyn, Richard V.; Langemeier, Michael R.
Abstract : This study evaluates the Adjusted Gross Revenue-Lite (AGR-Lite) whole-farm adjusted gross revenue insurance program on net farm income risk using panel data from 49 southeast Kansas beef farms. On average for the group, but not each individual farm, AGR-Lite reduces the mean and standard deviation of net farm income, raises the average minimum, and lowers the average maximum observations of the net income distribution. Thirty-four farms (69%) received at least one indemnity payment. Stochastic efficiency with respect to a function reveals that AGR-Lite is preferred by 18 of the farm managers (37%) when an upper bound on the risk-aversion coefficient is used.